2017
DOI: 10.3390/atmos8020037
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Heat Waves and Cold Spells over 1951–2015 in Guangzhou, China

Abstract: Abstract:The global climate has changed significantly, characterized by the warming of the surface air temperature, which seriously affects public health. We examined the trends of extreme temperatures, heat waves and cold spells in a subtropical city of Guangzhou, China, during 1951. Specifically, the relationship between ENSO (El Niño-Southern Oscillation) events and heat waves/cold spells was discussed. The results of linear regression showed the annual mean temperature and extreme warm days increased (0.14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 37 publications
1
8
0
4
Order By: Relevance
“…Other definitions vary, including the use of standard deviations (Vavrus et al ., ). Cold spell changes have been reported on regional scales (e.g., Europe, de Vries et al ., ; China, Zhang et al ., ; Northeast United States, Thibeault and Seth, ) and for global scales (Vavrus et al ., ; Konrad, ) using GCM ensembles and long‐term climate records. In most cases, cold days have shown decreases, and notably in Northern latitudes, it has been found that accelerated decreases of cold spells outpace increases in summer maxima (Thibeault and Seth, ).…”
Section: Extreme Temperature and Humiditymentioning
confidence: 99%
“…Other definitions vary, including the use of standard deviations (Vavrus et al ., ). Cold spell changes have been reported on regional scales (e.g., Europe, de Vries et al ., ; China, Zhang et al ., ; Northeast United States, Thibeault and Seth, ) and for global scales (Vavrus et al ., ; Konrad, ) using GCM ensembles and long‐term climate records. In most cases, cold days have shown decreases, and notably in Northern latitudes, it has been found that accelerated decreases of cold spells outpace increases in summer maxima (Thibeault and Seth, ).…”
Section: Extreme Temperature and Humiditymentioning
confidence: 99%
“…Mahdi and Dhekale () and Zhang et al . () used fixed temperature thresholds to identify CWs and HWs . Other recently published studies analysed both CW and HW (Barnett et al ., ; Keevallik and Vint, ; Lhotka and Kyselý, ; Oleson et al ., ; Spinoni et al ., ; Unkašević and Tošić, ; Ceccherini et al ., ; Plavcová and Kyselý, ; Capozzi and Budillon, ; Pereira et al ., ; Song et al ., ) and used temperature threshold based on percentiles.…”
Section: Methodsmentioning
confidence: 99%
“…(), HW is defined as the time when the minimum and/or maximum temperatures are higher than the 90th percentile for at least 3 days. Recent studies have applied the same method to two extreme temperatures in order to identify and classify CWs and HWs (Barnett et al ., ; Keevallik and Vint, ; Lhotka and Kyselý, ; Oleson et al ., ; Spinoni et al ., ; Unkašević and Tošić, ; Basarin et al ., ; Ceccherini et al ., ; Mahdi and Dhekale, ; Plavcová and Kyselý, ; Capozzi and Budillon, ; Pereira et al ., ; Zhang et al ., ; Song et al ., ). In other words, the threshold temperature that characterizes a HW is in the 90th percentile, and that of a CW is in the 10th percentile.…”
Section: Introductionmentioning
confidence: 98%
“…In 2014, an unprecedented outbreak of dengue fever occurred in Guangzhou, causing 37,305 cases of infections [30]. This outbreak was attributed to the combined effects of the urban heat island and climate change, including more frequent and intense heat wave events [31].…”
Section: Methodsmentioning
confidence: 99%